Eye contact during live social interaction modulates infants’ oscillatory brain activity - Höhl, Stefanie; Michel, Christine; Reid, Vincent M.; Parise, Eugenio; Striano, Tricia (Social neuroscience, 2014)
We examined infants’ oscillatory brain activity during a live interaction with an adult who showed them novel objects. Activation in the alpha frequency range was assessed. Nine-month-old infants responded with desynchronization of alpha-band activity when looking at an object together with an adult during a social interaction involving eye contact. When infant and experimenter only looked at the object without engaging in eye contact, no such effect was observed. Results are interpreted in terms of activation of a generic semantic knowledge system induced by eye contact during a social interaction.